Briefing Idea of Geopolitics - Mizan, Md.Mizanur Rahman (International Journal of Sustainable Applied Sciences, 2024)
Geopolitical diversity holds an undeniable allure, leading to the categorization of publications into four 'schools': neo-classical geopolitics, subversive geopolitics, non-geopolitics, and critical geopolitics, each exploring different dimensions of geopolitical dynamics. These schools distinguish themselves based on their proximity to the studied object (practical/applied or academic/reflective) and their stance toward the state system (focusing on states as principal actors or acknowledging other political actors and interests). Despite their differences, these studies collectively demonstrate a growing interest in geo-economics. Various thinkers, including Mackinder, Spykman, Collins, and Ratzel, have formulated these theories using terms like Heartland, Rimland, inland, outerland, enclave, and exclave. Notably, Bangladesh, as a developing country, is geopolitically strengthening its position in world politics.